Single stage Anterior Sagittal Anorectoplasty (ASARP) for Anorectal Malformations with Vestibular Fistula and Perineal Ectopic Anus in Females: A New Approach - Chaudhary, Ramananda Prasad; Thapa, Bijay; Thana, Santosh; Singh, Pradeep B (Journal of Nepal Paediatric Society, 2009)
Introduction: Despite a better understanding of the embryology, anatomy of anorectal malformations and of the physiology of continence, the management of children born with imperforate anus continues to be a surgical challenge and is still fraught with numerous complications and often leads to less than perfect qualitative results. Pediatric patients with recto-vestibular fistula have good prognoses in terms of bowel function when properly treated. Aim & Objective: The study was designed to assess the surgical morbidity of single stage Anterior Sagittal Anorectoplasty (ASARP). Methodology: This prospective study was carried for a period of 26 months. It included a total of 48 female patients (aged 0 - 14 years) with diagnosis of Anorectal Malformations (ARM) with vestibular fistula or perineal ectopic anus. In ASARP, Patient in lithotomy position, the anterior portion of sphincter muscles were cut through a midline perineal skin incision, rectum was separated from the vagina & then rectum was pulled through the center of these muscles. The perineal body was reconstructed and the normal appearance of perineum was achieved. Results: Short-term surgical outcome was satisfactory in all cases. No one needed colostomy. Conclusion: Single-stage ASARP is a good approach in experience hands for ARM with vestibular fistula and perineal ectopic anus in females and thereby complications and time involved in staged procedures including colostomy can be avoided. Key words: Anterior sagittal anorectoplasty, anorectal malformations, perineal ectopic anus, vestibular fistula. DOI: 10.3126/jnps.v30i1.2458 Journal of Nepal Paediatric Society Vol.30(1) 2010 37-43